Environmental state and tendencies of the Puerto Morelos CARICOMP site, Mexico - Rodríguez-Martínez, Rosa E (2010)
The CARICOMP site at Puerto Morelos, Mexico was monitored from 1993 to 2005. No significant changes in air temperature, wind patterns, periodicity and quantity of rainfall, sea-surface temperature and water transparency were observed between sampling years. During the study four hurricane impacts were registered. At the coral reef site overall mean cover of fleshy algae (47%) and turf algae (36%) were high, whereas cover of corals (2%) and sponges (3%), and abundance of sea-urchins (0.04 org m-2) were consistently low. Gorgonians were dominant and showed changes in their community structure; the number of species increased from 1993 to 1995, their abundance decreased after Hurricane Roxanne (1995) and recovered by 2001. At four seagrass sites total community biomass remained constant (707.1-929.6 g dry m-2) but the above-ground biomass of the seagrass Syringodium filiforme and fleshy algae increased gradually. Total biomass (531-699 g dry m-2) and leaf productivity (0.89-1.56 g dry m-2 d-1) of the seagrass Thalassia testudinum remained constant, but the species invested proportionally more biomass in above-ground leaf tissues at the end of the study. The minor hurricanes from 1993 until 2005 had no detectable impacts on the seagrass beds, however, the major Hurricane Wilma (October 2005) changed the community composition at three stations and caused complete burial of the vegetation at a coastal station. The gradual changes in the seagrass and reef communities recorded in the 12 years of continuous monitoring of the CARICOMP site may reflect the increased pollution caused by the rapid augment in urban and tourist developments along the coasts and inland from Puerto Morelos, coupled with poor water management practices.